2001
DOI: 10.1063/1.1377875
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of the protolytic dissociation of HCl in water clusters

Abstract: Reaction mechanisms for the acidic dissociation of HCl in water clusters are considered. Intermediates in the reaction are obtained from stationary points on the potential energy surface of the systems HCl-͑H 2 O͒ n with nϭ4 and 5. These points have been determined by the B3LYP density functional method in an aug-cc-pVDZ atomic orbital ͑AO͒ basis. The total energies of the stationary points are checked by the coupled cluster single-double-triple ͓CCSD͑T͔͒ method in the same AO basis. For the case of nϭ4 a mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
114
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(130 citation statements)
references
References 37 publications
13
114
1
Order By: Relevance
“…19 Using the B3LYP density functional method and the CCSD(T) ab initio method, Milet et al showed however that HCl starts dissociating already in HCl(H 2 O) 4 . 20 Devlin et al, using ab initio Monte Carlo simulations found that in HCl-(H 2 O) 6 three-coordinated HCl dissociates directly to form a clearly recognizable solvated Cl -and H 3 O + ion pair. 21 They also suggested that to induce ionization, HCl must bind to a two-coordinated dangling-O molecule, that is, one that does not accept a proton from another H 2 O molecule.…”
Section: Introductionmentioning
confidence: 99%
“…19 Using the B3LYP density functional method and the CCSD(T) ab initio method, Milet et al showed however that HCl starts dissociating already in HCl(H 2 O) 4 . 20 Devlin et al, using ab initio Monte Carlo simulations found that in HCl-(H 2 O) 6 three-coordinated HCl dissociates directly to form a clearly recognizable solvated Cl -and H 3 O + ion pair. 21 They also suggested that to induce ionization, HCl must bind to a two-coordinated dangling-O molecule, that is, one that does not accept a proton from another H 2 O molecule.…”
Section: Introductionmentioning
confidence: 99%
“…One inquiry that persistently threads its way through this subject is: what is the minimum quantity of water molecules, (H 2 O) n , required to dissociate the acid [18]? According to calculations, the acidically dissociated structure is supported starting from n=4; most of the theoretical approaches agree that at this size the dissociated form represents the global minimum on the potential energy surface [18][19][20][21][22][23][24]. Experimentally, for neutral clusters the question has been probed by laser spectroscopy (see, e.g., [25][26][27][28]) but finding a conclusive spectroscopic signature of the onset of dissociation in a nanocluster is not straightforward.…”
Section: Introductionmentioning
confidence: 99%
“…Even more than in the water trimer, the three-body effects are considerable 66 in the very polar system HCl-͑H 2 O͒ 2 . Consequently, the results of a study on the trimer will be useful for larger clusters, as the most important interactions, the pair-and the three-body interactions, are present in the trimer.…”
Section: Introductionmentioning
confidence: 99%